Role of fine needle aspiration cytology and cytohistopathological co-relation in thyroid lesions: experience at a tertiary care centre of North India - Chandra, Smita; Mahajan, Divya; Chandra, Harish (International Journal of Research in Medical Sciences, 2016)
Background: Fine needle aspiration cytology is considered to be simple and cost effective technique for diagnosis of thyroid lesions. However the common limitations which may be encountered in FNAC may be associated with sampling error, dual pathology, cystic change or misinterpretation of morphology. The present study was therefore conducted to study the role of FNAC in diagnosis of thyroid lesions and to study the diagnostic pitfalls which may be encountered that limit the diagnosis of thyroid lesions. Methods: A retrospective study was conducted which included all the cases of thyroid lesions in which FNAC was done either directly or under image guidance over a period of five years. The cytomorphological diagnosis was correlated with histopathology to assess the diagnostic accuracy of FNAC in diagnosis of thyroid lesions. Results: Colloid goitre was the most common benign thyroid lesion while papillary carcinoma was the most common carcinoma constituting 50.2% and 5.2% of total cases. The maximum cyto-histopathological discordance was observed in cases of autoimmune thyroiditis (38%) and papillary carcinoma was most common lesion which was underdiagnosed on FNAC. Conclusions: The study concludes that although FNAC is safe, cost effective and sensitive technique for diagnosis of thyroid lesions but vigilant cyto-morphological interpretation in association with skilful aspiration and clinic-radiological co-relation is essential to avoid diagnostic pitfalls. This is even more important in cases showing focal neoplastic pathology or presence of dual pathology. Repeat image guided FNAC with clinical follow up is recommended in cases with strong clinical suspicion of malignancy.